Effectiveness and Role of Symbiotic Culture of Bacteria and Yeast (SCOBY) Kombucha Gel on Incisional Wound Healing in Mice (Mus musculus) - Nafisah, Raihana Frika; Agustina, Eva; Purnamasari, Risa; Andiarna, Funsu; Hidayati, Irul (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2025)
Incision wounds are common occurrences in daily life, and appropriate wound management is essential to promote and accelerate the healing process. Wound care can be performed using topical preparations such as gels containing bioactive compounds. SCOBY kombucha is believed to contain bioactive compounds, such as compounds from green tea (especially polyphenols) and metabolites produced by microbes (organic acids, alcohols, vitamins, etc.) The aim of this research is to determine the effectiveness of SCOBY kombucha gel on the healing of incision wounds in mice (Mus musculus). The method used in this research is a Completely Randomized Design (CRD) with 8 treatment groups, including 2 control groups and 6 test groups. The concentrations of SCOBY kombucha gel used are 0%, 2%, 4%, 8%, 10%, and 12%. The SCOBY kombucha gel is applied twice daily until the wound closes. Observation of the incision wound is carried out by measuring the length of the wound that has not yet closed. Based on the conducted research, it was found that SCOBY kombucha gel is effective in healing incision wounds as evidenced by the reduction in wound size due to the bioactive compounds in SCOBY. The most significant wound healing effect was observed with the 12% SCOBY kombucha gel, as there was a significant difference compared to the negative control group, 0%, 2%, 4%, and 8% SCOBY kombucha gels.